Leadership Excellence For SME’s Growth - Shingate, Amol (Digital Repository of Theses, 2025)
This dissertation investigates the role of leadership excellence in the growth of Small and Medium Enterprises (SMEs) in India. Using a mixed-methods explanatory sequential design, qualitative insights from 20 semi-structured interviews informed the development of a quantitative survey administered to 385 SME leaders across five states. Findings confirm that Emotional Intelligence (EI) and Transformational Leadership (TL) significantly predict SME performance, innovation, and employee retention. Results from Structural Equation Modeling (SEM) indicate a strong positive path from EI to SME growth and from TL to innovation outcomes. The study contributes both theoretically and practically, offering a tailored framework for SME leadership development in the Indian context.